2013
DOI: 10.1111/1744-9987.12090
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Refusing Kidney Transplantation Among Chronic Dialysis Patients

Abstract: The aim of the prospective clinical study was to evaluate the reasons for refusing kidney transplantation among chronic dialysis patients. A total of 164 adult chronic dialysis patients participated in the study. They were asked to complete a detailed questionnaire on specific issues regarding transplantation. The mean age was 60.9 ± 16.0 (20-89) years, 61.6% were male, 11.6% had had a previous transplant. The majority, that is, 72.0%, of the patients believed that transplantation improved the quality of life,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…As has been shown before in previous study, age was a factor in refusal of renal transplantation [5]. Patients who are employed tend to accept renal transplantation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As has been shown before in previous study, age was a factor in refusal of renal transplantation [5]. Patients who are employed tend to accept renal transplantation.…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, other study reported that side effects of immunosuppressive medications are a major reason behind refusal of renal transplantation among ESRF patients [5].…”
Section: Discussionmentioning
confidence: 88%
“…The relative young age of applicants for kidney transplantation was also mentioned by other authors [10] [21]. Patients on dialysis for long period were willing to kidney transplantation.…”
Section: Discussionmentioning
confidence: 69%
“…While the results of the western studies explain the rejection of kidney transplantation by the fear of the immunosuppression and uncertainty related to the development of the transplantation [10], or a previous personal or somebody else bad experience [21], our patients lay the emphasis upon the high cost of the transplantation. The high cost of kidney transplantation compared to dialysis was also mentioned by patients in other African countries [12] [15] [16], China [9] and in the African American community [11] of USA.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation